Obstacle Avoidance for Vision-Based Automated Guided Vechicle (AGV) Using Shortest path Planning - Mohd Shah, Hairol Nizam; Sulaiman , Marizan; Syed Salim , Syed Najib (2008)
This paper dscribes an obstacle avoidance technique for Automated Guided Vehicle (AGV).